Functional relationship between crop raiding by the savannah elephant and habitat variables of the Red Volta Valley in north-eastern Ghana - Adjewodah, Patrick; Oduro, William; Asase, Alex (Pachyderm, 2012)
We investigated the degree to which crop raiding by elephants in the Red Volta Valley is a function of: the density and diversity of their natural browse, extent of degradation of their habitat, and proximity of crop enclaves to the nearest forest boundary. We assessed 50 m x 5 m quadrats for browse and for agents of degradation (m 2 of quadrat area clear-felled, burned, and surface mined), and we adopted records of crop-raiding rates in 2000–2002 for correlation with habitat variables. We estimated the distance of affected enclaves from the forest, river and village using GIS; the total size of crop fields in a locale provided an estimate of the extent of cultivation. Using correlation and regression analysis, we examined for each locale the association between rate of crop-raiding incidents and the density and diversity of browse, size of crop fields, and distance of affected enclaves from the forest, river and village. We used a stepwise regression model to establish a functional relationship between crop raiding and the enumerated habitat variables. Second-order jackknife and Michaelis-Menten asymptotic estimators showed that the density and diversity of browse was near optimum. About 99% of the vegetation area sampled was burned, and 0.35 ha of vegetation was clear-felled for firewood. No evidence of mining was recorded. There was a significant inverse association between crop raiding and distance of affected enclaves from the forest, while the association between crop raiding and density and diversity of browse and the extent of degradation were not significant. A stepwise regression model gave a functional relationship between the observed rate of crop-raiding incidents and proximity of crop enclaves to the forest as Y = 25.105 + 3.2 – 9.73X (Y = rate of crop-raiding incidents and X the distance from enclave to the forest boundary). Contrary to speculation, crop raiding in the study area is not influenced by the status of browse, extent of degradation or size of cultivated fields. Thus, mitigation measures should include relocating farms away from forest reserves, while measures aimed at reducing the density of farms or replanting of the forest should be de-emphasized as they will not necessarily reduce crop raiding. Additional key words: locale, enclave Nous avons étudié la mesure dans laquelle la maraude des cultures par les éléphants dans la vallée de la Volta Rouge dépend de: la densité et la diversité de leur broutage naturel, l’ampleur de la dégradation de leur habitat et la proximité des enclaves de cultures à la limite de la forêt la plus proche. Nous avons évalué des quadrats de 50m x 5m pour le broutage et les agents de dégradation (m 2 de superficie de quadrats coupés àblanc, brûlés, et la surface exploitée par les mines), et nous avons adopté des données des taux de maraude des cultures de 2000 à 2002 pour la corrélation avec les variables d’habitat. Nous avons estimé la distance des enclaves affectées à partir de la forêt, de la rivière et du village en utilisant le SIG. La superficie totale des champs cultivés dans un endroit a donné une estimation de l’étendue des cultures. En utilisant la corrélation et l’analyse de régression, nous avons examiné pour chaque endroit l’association entre le taux d’incidents de maraude des cultures et la densité et la diversité du broutage, la superficie des champs cultivés, et la distance des enclaves affectées à partir de la forêt, de la rivière et du village. Nous avons utilisé un modèle de régression par étapes pour établir une relation fonctionnelle entre la maraude des cultures et les variables énumérés de l’habitat. Des estimateurs asymptotiques de second ordre de Jackknife et de Michaelis-Menten ont montré que la densité et la diversité du broutage étaient quasi optimales. Environ 99% de la zone couverte de végétation échantillonnée avait été brûlée, et 0,35ha de végétation avait été coupée à blanc pour le bois de chauffage. Aucune preuve de l’exploitation minière n’a été enregistrée. Il y avait une association inverse significative entre la maraude des cultures et la distance des enclaves affectées à partir de la forêt, tandis que l’association entre la maraude des cultures, la densité et la diversité du broutage, et l’ampleur de la dégradation, n’étaient pas significatifs. Un modèle de régression par étapes a donné une relation fonctionnelle entre le taux observé d’incidents de maraude des cultures et la proximité des enclaves cultivées de la forêt de Y=25.105+3.2–9.73X (Y = taux d’incidents de maraude des cultures, et X la distance de l’enclave à la limite de la forêt). Contrairement aux spéculations, la maraude des cultures dans la zone d’étude n’est pas influencée par l’état du broutage, l’ampleur de la dégradation ou la superficie des champs cultivés. Ainsi, les mesures d’atténuation devraient inclure la délocalisation des fermes loin des réserves forestières, tandis que les mesures visant à réduire la densité des exploitations agricoles ou la replantation de la forêt sont moins importantes car elles ne réduiront pas nécessairement la maraude des cultures. Mots clés supplémentaires: endroit, enclave